The cicadas (Hemiptera: Cicadidae) of Trinidad and Tobago including the description of three new species and seven new records, with new records for several additional Caribbean Islands - Sanborn, Allen F. (Zootaxa, 2020)
The known cicada fauna of the Republic of Trinidad and Tobago is identified. Calyria hyperochelabrys n. sp., Carineta trinidadensis n. sp., and Herrera grammosticta n. sp. are described as new. The first records of Fidicinoides descampsi Boulard & Martinelli, 1996, Proarna hilaris (Germar, 1834), Guyalna bogotana (Distant, 1892a), Majeorona aper (Walker, 1850), Taphura boulardi Sanborn, 2011a, Carineta matura Distant, 1892b, and Herrera nigropercula Sanborn, 2020b are provided. The first reports for the genera Guyalna Boulard & Martinelli, 1996, Majeorona Distant, 1905d, Calyria Stål, 1862, Carineta Amyot & Audinet-Serville, 1843 and Herrera Distant, 1905c and the tribes Parnisini Distant, 1905e and Carinetini Distant, 1905c are represented by the records for the new species and new records. The first records of Proarna hilaris (Germar, 1830) for Anegada, Antigua, Grenada, Canoun Island, Mayreau Island and Union Island in the Grenadines, Little St. James, Little Thatch Island, Montserrat, Mosquito Island, and St. Kitts, Proarna palisoti (Metcalf, 1963a) for Navarro Island, Majeorona aper (Walker, 1850) for Grenada, and Ariasa albimaculosa Sanborn, 2016c for Bonaire are provided to increase the known distributions of these species and the Caribbean fauna. The currently known cicada fauna for Trinidad is increased here to 15 species representing ten genera, four tribes and two subfamilies. Only Quesada gigas (Olivier, 1790) is known currently from Tobago.